Isn’t it time for Quantity Surveyors to contribute to Sustainability? - Khan, Laiba; Tong, Nguyet; Phung, Quan (International Journal of Sustainable Construction Engineering and Technology, 2024)
The construction industry faces criticism for its slow adoption of sustainable development, sparking global discussions on shifting from traditional practices to sustainable construction practices (SCP). With enhanced support and knowledge in sustainability, Quantity Surveyors (QS) have the potential to significantly influence SCP implementation, leveraging their in-depth understanding of building life-cycle costing. However, despite their crucial skills and potential to contribute to sustainable development goals, their role remains under-recognised in much of the literature and industry practice. This research seeks to explore ways in which QS can enhance their influence on SCP implementation within the construction sector. This is accomplished through a comprehensive literature review and semi-structured interviews with QS professionals from diverse organisations involved in both public and private UK projects. The findings highlight four key limiting factors—Cost Consideration, Stakeholder Influence, Standardisation, and Knowledge—that restrict QS influence in implementing SCP. A deeper insight into these factors empowers QS to more effectively drive SCP implementation in construction projects.